Olfactory eavesdropping: The odor of feathers is detectable to mammalian predators and competitors. (12th October 2017) - Mihailova, Milla; Berg, Mathew L.; Buchanan, Katherine L.; Bennett, Andrew T. D.
Abstract: The role of olfactory eavesdropping in interactions between mammalian predator and prey species is well established. Bird plumage can be odorous and consequently nest predators could use odor to identify and locate avian prey, and nest competitors could use odor to assess occupancy of nest cavities by birds. However, despite extensive research on avian nest predation and competition, the costs of olfactory eavesdropping on plumage odor by nest predators or competitors remain largely unknown. We used two experiments to investigate whether feather odor is detected by marsupial species which are competitors for nest hollows and predators of eggs and nestlings of crimson rosellas, Platycercus elegans . In the first experiment, odor presentation at nest boxes utilized by ringtail possums ( Pseudocheirus peregrinus ) and rosellas showed that the latency of possums to enter the nest was shorter when crimson rosella odor was present compared to the controls. In the second experiment, carried out away from nest hollows, brushtail possums ( Trichosurus vulpecula ) discriminated odors of two predators (dingo, Canis lupus dingo, and cat, Felis catus ) from crimson rosella and control odors; however, they did not discriminate between crimson rosella odor and a control. We show that marsupials may use feather odor cues to assess nest hollow status, information which could aid their detection of avian prey or their vigilance at nest hollows (for which they compete with parrots). To our knowledge, our study is the first to show that wild mammalian predators and competitors of birds respond to plumage odor at nests and suggest that odor signaling may have hitherto unrecognized costs for birds.